Strategi Pemanfaatan Teknologi Digital untuk Mendukung Ekspansi Internasional pada Usaha Kecil dan Menengah - Edi Irawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Digitalization has been a key catalyst for change in the global business landscape, driving the transformation of companies' strategies, organizational structures, and operational models. For small and medium enterprises (SMEs), digital technology opens up great opportunities to expand market reach and compete in the international arena more effectively. Technologies such as e-commerce, social media, big data analytics, and cloud-based platforms enable SMEs to break through geographical boundaries, facilitate access to global customers, and accelerate product distribution and marketing processes. This paper explores the current academic literature that discusses the influence of digital technology on the internationalization of SMEs. A total of five relevant studies were analyzed to identify common patterns, challenges, and successful strategies in the use of digital technology. The results of the study show that the adoption of digitalization not only improves operational cost efficiency, but also encourages business model innovation, such as digital platform-based marketing, cross-border virtual collaboration, and the development of a more adaptive global business ecosystem. In addition, the ability to utilize digital technology gives SMEs a competitive advantage through access to real-time market information, personalization of offers, and more targeted branding strategies. However, the research also found obstacles, such as limited human resources, technological infrastructure, and digital literacy among SMEs. Therefore, synergy is needed between business actors, the government, and academia to support the acceleration of digital technology adoption through training, mentoring, and policies that support innovation. The paper also highlights future research opportunities, such as the integration of artificial intelligence (AI) technologies, automation, and blockchain in supporting the global expansion of SMEs. These findings are expected to be a strategic reference in designing sustainable internationalization policies in the digital era.